Cellular immune responses in mice immunized with Anisakis simplex larval antigens - Perteguer, M. J.; Rodero, M.; Flores, J. M.; Dorea, RCC; Cuellar, C. (Springer, 2001)
Cellular immune responses to Anisakis simplex L3 antigens were investigated in BALB/c mice injected subcutaneously with a homologous crude extract (CE). Popliteal lymph nodes (PLN) were found to be increased in size and weight after A. simplex CE footpad injection. The effects of A. simplex CE in vitro proliferation were assayed with non-fractionated PLN cells or nylon-wool purified T cells derived from pooled lymph node cells of mice subcutaneously injected with CE. Spleen cells from immunized animals (antigen alone, or larva alone, or antigen plus larva) were studied by flow cytometry. The immunization induced a high proportion of CD4 + and TCR alpha beta + T cells. The number of B cells (CD45 + and TCR alpha beta-) in pre-immunized and infected mice was lower than that observed in animals subjected to infection only. The number of CD4 + T cells increased in the infected and in the pre-immunized and infected mice. In the latter, a decrease of CD8a + T cells was noted. The greatest increase in CD8a+ and TCR alpha beta- T cells was found in mice that had been subjected to infection only. Histological analysis showed that the most prominent lesions were gastric and intestinal in animals infected orally with one larva.